2020
DOI: 10.1177/1470785320938293
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of services and apps on mobile phones by micro-entrepreneurs in Sub-Saharan Africa

Abstract: This article shows that acquisition pattern analysis is highly suited for research in developing economies. Consumers in such contexts prioritize the adoption of alternative product-services as a result of resource constraints. In the reported acquisition pattern analysis, we provide insights into sequential adoption of services and applications (apps) on mobile phones, for example, Facebook and mobile money, by micro-entrepreneurs in Sub-Saharan Africa. We collected survey data from 169 Zambian food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 62 publications
(109 reference statements)
0
4
0
Order By: Relevance
“…Regarding the antecedents of the use of mobile phones and apps for service purposes, it was found that the adoption of services and apps is driven by individual’s mobile phone technology maturity and business development (Paas et al 2021 ). An analysis of user’s feedback on Twitter of four prominent food delivery apps and app store reviews of these apps revealed that the main concerns of users are related to issues regarding customer service, orders, food, delivery, time, app, money, drivers, and restaurants (Williams et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the antecedents of the use of mobile phones and apps for service purposes, it was found that the adoption of services and apps is driven by individual’s mobile phone technology maturity and business development (Paas et al 2021 ). An analysis of user’s feedback on Twitter of four prominent food delivery apps and app store reviews of these apps revealed that the main concerns of users are related to issues regarding customer service, orders, food, delivery, time, app, money, drivers, and restaurants (Williams et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Africa Cameroon [118] Africa Not specified [119] Africa Mozambique [120] Africa Sub-Saharan Africa [121] Africa Ghana, Kenya, Lesotho, Mozambique, Nigeria, Rwanda, Senegal, Tanzania and Uganda [122] Africa Not specified [123] Africa South Africa [124] Africa South Africa [128] Africa Africa Tunisia…”
Section: Citation Continent Specific Region/country [74]mentioning
confidence: 99%
“…In QAM, studies of product portfolio developments addressed households’ acquisition of specific, durable product categories (Hebden and Pickering, 1974; Paroush, 1965); later studies analysed households’ financial product portfolios (Paas et al, 2007; Prinzie & Van den Poel, 2006), sequential customer adoption orders for mobile phone services (Paas et al, 2021), or consumer adoption of different green product categories (Juhl et al, 2017).…”
Section: Analytical Companies: Customer-centric ML Modelsmentioning
confidence: 99%